1984
DOI: 10.1007/bf00915283
|View full text |Cite
|
Sign up to set email alerts
|

Defective bactericidal activity and absence of specific granules in neutrophils from a patient with recurrent bacterial infections

Abstract: Recent studies have suggested that specific granules and/or their contents may have a role in neutrophil adherence, oxidative metabolism, and other aspects of cell function. In the current report, we studied neutrophil function in a 13-year-old female with recurrent pyogenic infections and absent specific granules previously documented by electron microscopy. Levels of cobalamin (vitamin B12)-binding protein and lactoferrin were markedly decreased in this patient's neutrophils. Bactericidal activity against Es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 31 publications
1
32
0
Order By: Relevance
“…2). Although total cell myloperoxidase, lysozyme, lactoferrin, and alkaline phosphatase were similar in patient neutrophils compared with those of healthy adult controls (7,8), the patient's neutrophils demonstrated a defect in azurophilic granule release in response to different stimuli. PMA-or fMLP-stimulated release of azurophilic granules (9), as measured by myloperoxidase, was completely absent (Fig.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…2). Although total cell myloperoxidase, lysozyme, lactoferrin, and alkaline phosphatase were similar in patient neutrophils compared with those of healthy adult controls (7,8), the patient's neutrophils demonstrated a defect in azurophilic granule release in response to different stimuli. PMA-or fMLP-stimulated release of azurophilic granules (9), as measured by myloperoxidase, was completely absent (Fig.…”
Section: Resultsmentioning
confidence: 86%
“…Supernatants were removed from the cells after centrifugation and assayed for myeloperoxidase (MPO) and lactoferrin (LF) by using a colorimetric assay and ELISA, respectively (7,8). Total cell content of alkaline phosphatase, lysozyme, MPO, and LF for 10 6 neutrophils was also measured (7)(8)(9). The amount of MPO and LF released into the supernatant was represented as a percentage of total cell content (7)(8)(9).…”
Section: Isolation Of Neutrophils and Neutrophil Subcellular Fractionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Skin lesions are often indolent, requiring months to heal. S. aureus is responsible for most infections, and P. aeruginosa is occasionally identified in cases of mastoiditis (12,101,149,265). Candida infections have been seen, but invasive fungal disease has not (46,101,149,215).…”
Section: Functional Neutrophil Disordersmentioning
confidence: 99%
“…For example, the golden pigment of S. aureus is an important virulence factor that shields the pathogen from host oxidative killing, and we have previously shown that blocking the biosynthesis of this pigment could be a strategy for treatment of S. aureus infection (4). Conversely, among human genetic conditions that alter susceptibility to S. aureus infection is neutrophil-specific granule deficiency (SGD), a rare hematologic disorder characterized by a significantly defective immunity (5)(6)(7)(8). Patients with SGD present with functional defects in neutrophils, as well as monocytes/macrophages, and suffer from recurrent life-threatening bacterial infections, including S. aureus, Pseudomonas aeruginosa, and Klebsiella pneumoniae.…”
Section: Introductionmentioning
confidence: 99%